Study of Conditions of Municipal Corporation Schools as Small Schools in the Vadodara City - Khirwadkar, Anjali (JOURNAL OF INDIAN EDUCATION, 2010)
Primary education occupies an important role in the life of an individual. It is the base on which further educational opportunities of a child depends. The process of primary education is an index of the general, social and economic development of the country as a whole. Primary education plays an important role in laying the proper foundation of child’s cultural, emotional, intellectual, moral, physical, social and spiritual development. Primary education contributes to national development also. Various studies have clearly demonstrated that countries which have made proper provision for primary education are far ahead with those of inadequate provision. Taking into consideration the importance of this part of education, Indian government has taken up several projects to achieve the goals of UEE. All of them have their own drawbacks in achieving the goal to full extent. Primary education being the fundamental stage of education is helpful in developing awareness among children about education through proper development of concepts.The aims and objectives are to focus more on joyful learning by developing proper curriculum and competent textbooks. At this juncture, the way teachers adopting the teaching-learning practice to provide the active playway method of education is crucial to achieve the goals of UEE. The present paper focuses on these aspects in a classroom situation.